(untitled) (American Journal of Chemistry and Pharmacy, 2025)
Healthcare logistics also had peculiar issues that needed some out-of-the-box solutions to improve transparency, data integrity, and efficiency. This research paper fixed these drawbacks by coming up with a Blockchain-Internet of Things (B-IoT) modeling of healthcare logistics, but with specific reference to drug supply and medical supplies. The combination of a decentralized, immutable ledger and real-time IoT monitoring enhances traceability, security, and automation in the pharmaceutical supply chains. In order to determine the effectiveness of this framework, the study used mixed approach where a literature review was used alongside interviews of experts, comprised of healthcare managers of logistics and technology developers and a regulatory consultant. The critical factors that were evaluated in the proposed framework are technologically rich infrastructure, data governance, interoperability, compliance regulations and cost-effectiveness. After the implementation of B-IoT, there was a major improvement noticed. The time taken in order processing was reduced by 75 percent 48 to 12 hours. Visibility of the supply chain improved to 137.5%, the shipment errors sank to 88 and instances of mismanagement of inventory decreased by 86.7. Besides, the total cost of logistics decreased by 25%, but cybersecurity costs increased by 20% and costs of training workforce increased by 200% as a result of the specialized training required of the workforce. It is worth mentioning that data and patient privacy breach issues were fully eradicated, which shows the effectiveness of the framework that helps to increase protection levels. Although these were the advantages, some challenges arose in form of high costs of integration, lack of technical expertise as well as regulatory barriers. The study suggested the use of phased implementation strategy (illustrated by pilot programs and targeted training initiatives) as a solution to such barriers. It was indicated that B-IoT technologies would be very promising in the area of healthcare logistics, which would be more marketable in efficiency, safety, and regulatory conformity, but additional investigations on scalability and cost-efficiency were required.